If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + 3b = b Solving 24 + 3b = b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 24 + 3b + -1b = b + -1b Combine like terms: 3b + -1b = 2b 24 + 2b = b + -1b Combine like terms: b + -1b = 0 24 + 2b = 0 Add '-24' to each side of the equation. 24 + -24 + 2b = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 2b = 0 + -24 2b = 0 + -24 Combine like terms: 0 + -24 = -24 2b = -24 Divide each side by '2'. b = -12 Simplifying b = -12
| x^6-2x^3-27=0 | | 10=ln(3X+7) | | 3b-24=0 | | w+13=28 | | 7/8=56 | | 3b+24=0 | | 2(3x-4)+6=4(x-3) | | 9x^2-32x=19 | | (-2x^7)(-3x^6)= | | 3(t-1/3)-4=6 | | (3x)(2x^3)= | | 5x-2=3x-10 | | -(-y+18)+11=1 | | (5x^2+11)-(9x^2-4)= | | 5/9x+83=4/9x+92 | | x+139=130 | | (5x^2-x-1)-(-3x^2-2x-4)= | | 7n-9=5 | | 21=4+t | | 6x+3=4x-9 | | (4x+5)-(5x-6)= | | 8x+2+130=180 | | (-10x+12)+(4x^2+10x-8)= | | -8=4(u+6)+4u | | t=dr+5 | | 8t^3-18t^2-18t=0 | | n/3-5=12 | | (-3x+4)+(-3x^2+3x-7)= | | -2v+2=-7v+17 | | 4(y-6)+3y=-38 | | -2=-4h+6 | | (6x-16)+(-14x+4)= |